2017
DOI: 10.2131/jts.42.53
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and surfactant protein-C expression inhibition induced by lipopolysaccharide in AEC II cell may associate with NF-κB pathway

Abstract: -Lipopolysaccharide (LPS), a Gram-negative bacterial outer membrane component, is one of the major causes of septic shock. Herein we investigate LPS-induced apoptosis of rat alveolar epithelial type II cells (AEC II) and the effects of LPS on surfactant protein-C (SP-C) expression in AEC II, along with the possible molecular mechanisms. LPS exposure impaired cell viability and increased apoptosis of AEC II significantly in concentration-dependent manner embodied in increased caspase-3 expression and the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Literature is not fully consistent in case of LPS influence on SP-C expression. One study has reported only a small impact on SP-C expression in LPS injured rat lungs [17]; the other one has found abnormally lower expression of SP-C in LPS-exposed ATII cells [13]. However, the impact of endotoxin on mRNA levels of all SPs in cultured pulmonary epithelial cells has still not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature is not fully consistent in case of LPS influence on SP-C expression. One study has reported only a small impact on SP-C expression in LPS injured rat lungs [17]; the other one has found abnormally lower expression of SP-C in LPS-exposed ATII cells [13]. However, the impact of endotoxin on mRNA levels of all SPs in cultured pulmonary epithelial cells has still not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…That is consistent with our previous experiments, in which at least a 1.5-fold decrease was present in the expression levels of all SPs in the lungs of rats with intratracheal instillation of LPS at the dose 500 µg/kg, while the administration of LPS at the dose 1000 µg/kg even further potentiated this effect [73]. As the molecular mechanism responsible for changes in SP expression, activation of the NF-κB pathway and the subsequent release of cytokines, has been suggested [13,15,72].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of SPs caused by bacterial products is thought to be mediated through IL-1 and TNF-α [ 36 , 37 ]. Moreover, LPS has been shown to reduce the viability of ATII cells [ 38 , 39 ] and modulate gene expression of all SPs [ 40 ]. Thus, the mechanism of reduced SPs gene expression is complex and may be related to increased levels of proinflammatory mediators, direct or indirect ATII cells damage, and reduced number of ATII cells due to their apoptosis and necrosis as the response to LPS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LPS affects the interaction between SP-B and lipids and thus reduce the expression and membrane function of SP-B [95]. In the same way, SP-C expression was abnormally lower in ATII cells of LPS-exposed rats [97]. ATII cells express functional receptors for LPS, such as TLR2 and TLR4 [86].…”
Section: Alveolar Epithelial Type II Cellsmentioning
confidence: 99%